(untitled) - Chandler, Raymond (New York, NY, 1995)
This volume also contains a screenplay, Double Indemnity, and a few essays and letters. The essays "The Simple Art of Murder", and "Writers in Hollywood" should be required reading for anyone interested in 20th century culture, movies, and literature
Keywords: Private investigators,Detective and mystery stories, American; Fiction; 20th century; California,Los Angeles